1974
DOI: 10.1073/pnas.71.10.4072
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of the Phospholipid Composition of Tissue Culture Cells

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
50
0

Year Published

1977
1977
1989
1989

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 23 publications
0
50
0
Order By: Relevance
“…Additional phosphatidylcholine mutants might be found by screening 5-10 times the number of colonies (i.e., 100,000 colonies or approximately 500 plates). A specific selection for phosphatidylcholine mutants would be invaluable, but unfortunately our results demonstrate that DNA and protein synthesis continued almost to the point of cell lysis (30)(31)(32)(33)(34)(35)(36) hr. Table 1).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Additional phosphatidylcholine mutants might be found by screening 5-10 times the number of colonies (i.e., 100,000 colonies or approximately 500 plates). A specific selection for phosphatidylcholine mutants would be invaluable, but unfortunately our results demonstrate that DNA and protein synthesis continued almost to the point of cell lysis (30)(31)(32)(33)(34)(35)(36) hr. Table 1).…”
Section: Discussionmentioning
confidence: 94%
“…These strains are defective either in CDP-diglyceridedependent phosphatidylserine sypthesis (26) or in phosphatidylethanolamine methylation (27,28), but neither of these pa.thways apparently plays a significant role in CHO cells. In this regard, most tnammalian lines, including CHO cells, require choline for growth (29,30 (Tables 1 and 2), the synthesis of other phospholipids continued for about 20 hr. Because sphingomyelin was also formed under conditions of CDP-choline depletion, the phosphorylcholine moiety of sphingomyelin may not be derived primarily from CDP-choline (31 …”
Section: Discussionmentioning
confidence: 99%
“…The pattern of incorporation of labeled acetate into the nonsaponifiable fraction was different from that observed for the fatty acid fraction of the total lipid extract from potato disks. When DME was added at zero time and the slices were pulsed at 2-hr intervals during aging, label incorporation was consistently inhibited from 30 to 40% compared with that of the control (Table VIII), similar to the case in mammalian cells (7).…”
Section: Resultsmentioning
confidence: 70%
“…Cerulenin (2S) (3R) 2,3 expoxy-4-oxo-7,10 dodecadienoylamide, an antibiotic produced by the fungus Cephalosporium coerulens, specifically inhibits fatty acid synthetase (1,3). Dimethylaminoethanol serves as an analogue of choline and in that role is incorporated into an analogue of lecithin (7,20). In what follows, it is shown that both of these agents inhibit the development of wound-induced respiration in a time-restricted manner, and it is deduced accordingly that phospholipid, and by extension membrane, biosynthesis are central elements in respiratory development in aging slices.…”
mentioning
confidence: 97%
“…For example, its fragility, antioxidative activity, and activities of receptors and enzymes in the membrane will be affected, resulting in cessation of cell growth followed by death [14].…”
Section: Resultsmentioning
confidence: 99%